HES1 is a novel interactor of the Fanconi anemia core complex - Tremblay, Cédric S. (Blood, 2008)
Fanconi anemia (FA) proteins are thought to play a role in chromosome stability and repair of DNA cross-links; however, these functions may not fully explain the developmental abnormalities and bone marrow failure that are characteristic of FA individuals. Here we associate the FA proteins with the Notch1 developmental pathway through a direct protein-protein interaction between the FA core complex and the hairy enhancer of split 1 (HES1). HES1 interaction with FA core complex members is dependent on a functional FA pathway. Cells depleted of HES1 exhibit an FA-like phenotype that includes cellular hypersensitivity to mitomycin C (MMC) and lack of FANCD2 monoubiquitination and foci formation. HES1 is also required for proper nuclear localization or stability of some members of the core complex. Our results suggest that HES1 is a novel interacting protein of the FA core complex.